Incising and Double Impregnation of Beech Sleepers—Investigation of an Alternative Preservation System for Wooden Railway Sleepers - Starck, Michael; Heidel, Andreas; Brischke, Christian; Militz, Holger (Frontiers in Forests and Global Change, 2022)
For nearly 200 years wooden railway sleepers are impregnated with creosote. After initially using vacuum pressure processes for impregnation, empty-cell processes have been developed quickly and are used until today. Because of political developments and its alarming properties against human health and environment the use of creosote is already restricted to certain industrial and commercially used products and will probably be banned on the European market and elsewhere in the near future. Today, most of the sleepers in track are concrete sleepers, but wooden sleepers are still essential for particular applications such as tracks with narrow curve radii, mountain tracks with uneven underground conditions and low ballast bed thicknesses, for switches, for railway bridges and for shunting stations. Without a successor product, wooden sleepers have to be installed either again without adequate protection against wood destroying organisms or will possibly be replaced by sleepers made from alternative materials like concrete, steel or polymers. The Fürstenberg-System-Sleeper, which combines a mechanical pre-treatment (incising), a double impregnation of sleepers including an alternative oily wood preservative and a water-borne copper salt as well as a modernized quality control shall on the one hand serve as an alternative to creosoted sleepers and on the other hand ensure future use of wooden sleepers in track superstructure. Incising reduced the formation of checks regarding their length, width, and depth in sleepers made from European beech (Fagus sylvatica L.) until they are sufficiently seasoned for impregnation. A decrease of the seasoning speed was not observed. During seasoning, the average global moisture content (MC) as well as the local MC showed hardly any differences between incised and not incised sleepers. Additionally, incising showed no influence on the dimensional stability, which would have reduced the number of sleepers being culled based on excessive deformation. Furthermore, positive effects on preservative retention and penetration were observed, where incising doubled the penetration depth up to over 30 mm and increased the mean retention from 46.5 to 72.0 kg/m3. During double impregnation with the water-borne preservative first and the oily preservative afterward, it became evident, that a gross weight of at least 950 kg/m3 was needed for penetrating the peripheral area of the sleepers to achieve an additional homogenous envelope treatment during the second impregnation with an average retention of approximately 30 kg/m3.